Genome-Wide Identification of Genes Probably Relevant to the Uniqueness of Tea Plant (Camellia sinensis) and Its Cultivars - Yan Wei; Wang Jing; Zhou Youxiang; Zhao Mingming; Gong Yan; Ding Hua; Peng Lijun; Hu Dingjin (International Journal of Genomics)
Tea (Camellia sinensis) is a popular beverage all over the world and a number of studies have focused on the genetic uniqueness of tea and its cultivars. However, molecular mechanisms underlying these phenomena are largely undefined. In this report, based on expression data available from public databases, we performed a series of analyses to identify genes probably relevant to the uniqueness of C. sinensis and two of its cultivars (LJ43 and ZH2). Evolutionary analyses showed that the evolutionary rates of genes involved in the pathways were not significantly different among C. sinensis, C. oleifera, and C. azalea. Interestingly, a number of gene families, including genes involved in the pathways synthesizing iconic secondary metabolites of tea plant, were significantly upregulated, expressed in C. sinensis (LJ43) when compared to C. azalea, and this may partially explain its higher content of flavonoid, theanine, and caffeine. Further investigation showed that nonsynonymous mutations may partially contribute to the differences between the two cultivars of C. sinensis, such as the chlorina and higher contents of amino acids in ZH2. Genes identified as candidates are probably relevant to the uniqueness of C. sinensis and its cultivars should be good candidates for subsequent functional analyses and marker-assisted breeding.